Characterization of teeth in a population with endodontic treatment attended in a university dental clinic using cone beam tomography and comparison with periapical radiography (Revista Nacional de Odontología, 2020)
Introduction: The images provided by radiographs are in two dimensions, which in many cases does not allow a real visualization of the anatomical conditions of the teeth and especially of the periapical tissues. This is why cone beam tomography can provide an image that allows better identification of the state of the teeth and their response to endodontic terpaia.Objective: To characterize teeth in a population treated by cone-beam tomography and comparison with periapical radiography.Materials and methods: A descriptive cross-sectional study, in which a detailed clinical examination was carried out, radiography and cone beam tomography were taken of patients who had previously been treated with endodontics, a descriptive analysis of the information was carried out, and concordance was evaluated, 0.56.Results: It is evidenced that the frequency of lesion by tomography was 29% while the diagnosis of radiographic lesion was presented in 19.4% of the analyzed teeth, it is also found that the highest frequency of injury reported By tomography it was presented in teeth with incomplete fillings, in the same way as in older ones in multiradicular teeth.Conclusion: cone beam tomography is a tool that is not yet widely used or recognized by clinicians in its diagnostic potential, and as a plan of endodontic case treatments.
Keywords: endodontics; radiography; cone beam; root anatomy; diagnosis